Bloom of a freshwater green alga Botryococcus braunii (Botryococcaceae, Trebouxiophyceae) and the associated mass fish mortality in a man-made lake, Sarawak, Malaysia - Teng, Sing Tung; Law, Ing Kuo; Afiqah Hamilton, Hanifah; Othman, Bojo; Farah Akmal, Idrus; Aini Hannani Naqiah, Abdul Mannaf; Lim, Po Teen; Leaw, Chui Pin (The Plankton Society of Japan, The Japanese Association of Benthology, 2021)
Mass mortality of fish (∼8,500 fishes), mainly Oreochromis placidus, was noted in a man-made lake located at Kuching, Sarawak (Malaysia). A field investigation was conducted to collect water samples and fishes. Patches of discoloration in brick red were observed in the lake and clear oil layer was found on the surface of the water. Microscopic observation and enumeration of the water samples showed that the plankton composition was dominated by a green algal species Botryococcus sp., with the colony densities ranging 1.2×103–7.4×106 colonies L−1. Detailed morphological assessment by light microscopy revealed the dominant species as Botryococcus braunii Kützing. Molecular characterization using an rDNA marker further supported the species identity as B. braunii in the L race. Fish gill observation showed that cells of B. braunii and the oily substances were found in the dead fish gills. The race-L B. braunii bloom was reported, for the first time, to be associated with a fish kill event in a freshwater lake in Malaysia and confirmed the species as one of the algal types causing harmful effects to the environment.